Facile synthesis of 4-substituted 1, 2, 4, 5-tetrahydro-1, 4-benzodiazepin-3-ones by reductive cyclization of 2-chloro-N-(2-nitrobenzyl)acetamides. Issue 3 (17th January 2019) - Sasiambarrena, Leandro D.; Barri, Ivan A.; Fraga, Guido G.; Bravo, Rodolfo D.; Ponzinibbio, Agustín
Graphical abstract: Highlights: N -substituted N -(2-nitrobenzyl)amines were prepared from o -nitrobenzaldehyde. 2-Chloro- N -(2-nitrobenzyl)acetamides exist as a two rotamers mixture in solution. Reductive Cyclization provides an easy method to achieve 1, 4-benzodiazepinones. New 1, 2, 4, 5-tetrahydro-1, 4-benzodiazepin-3-ones were prepared and characterized. Abstract: A facile and efficient method was developed for the synthesis of 1, 2, 4, 5-tetrahydro-1, 4-benzodiazepine-3-ones from 2-chloro- N -(2-nitrobenzyl)acetamides through a reductive cyclization using iron-ammonium chloride in ethanol–water in good yields. This method provides a simple approach to these benzodiazepine-3-ones which are of high value in the field of medicinal chemistry research.